Poetics and politics of Sufism and Bhakti in South Asia : love, l oss, and liberation - Panjabi, Kavita; Jadavpur University. Department of Comparative Literature; Victoria Memorial (Museum : India) (Kolkata : Orient BlackSwan, 2011)
Contributed papers presented at a seminar on Feb. 8-10, 2006, organi zed by Assisatance for Strengthening of Infrastructure for Humanities and Social Sciences Program, Dept. of Comparative Literature, Jadavpur University, in collaboration with the Victoria Memorial Hall and others .
Includes bibliographical references and index.
Keywords: Poetics; Poetry -- Collections -- South Asia; Politics and literature -- South Asia